Therapeutic Health Benefits of Religion Among Elderly- A Population based Representative Survey from Iran - Adeleh Sadeghloo1 , Somayyeh Meshkani 2 Hamid Hojjati 3, Devender Bhalla4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: We determined whether practice of religious beliefs influence health-related lifestyle among general elderly population. Methods: We recruited elderly (60+years) subjects from among the general population who were invited to answer practice of religious belief and healthy lifestyle in Iranian elderly questionnaires. Results: A total of 218 elderly subjects participated (51.3% males, mean age: 68.3 years, SD 9.2, range 60-92). The mean religious belief was 73.0 (SD 11.5) without male-to-female difference (p=0.9). The mean lifestyle was 100.9 (SD 14.7, range 61-138) with a 9.3% male-to-female difference, p=0.0001. The odds of better lifestyle with religion was 5.5 (p=0.001, effect-size=0.18, variance=29.5%). The most benefit was in prevention (effect-size 0.18), nutrition (effect-size 0.15), and social relationship (effect-size 0.12). Conclusions: Based on a representative un-selected validated sample, and by using a systematic questionnaire, and after controlling for various possible confounders, and within current evaluation limits, we may conclude that religion may mitigate health-related lifestyle.